PENGARUH BUDAYA ORGANISASI DAN KETERLIBATAN KARYAWAN TERHADAP KOMITMEN ORGANISASI (Studi Kasus Karyawan Medis Rsia Eria Bunda Pekanbaru) - Nur Latifah Damayanti; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study aims to determine the effect of organizational culture and employee involvement and its effect on organizational commitment (Case study of medical employees of RSIA Eria Bunda Pekanbaru). This study used a questionnaire as a data collection tool which was distributed to 57 medical employee respondents at RSIA Eria Bunda Pekabaru. The data is then processed using descriptive analysis and statistical analysis using SPSs by performing validity tests, reliability tests, simple linear regression analysis, multiple linear regression analysis, determination analysis (R2), and hypothesis testing with t test (Partial Test) and F test ( Simultaneous test).               The results showed that testing the hypothesis of organizational culture had a significant effect on organizational commitment of medical employees of RSIA Eria Bunda Pekanbaru, job involvement had a significant effect on organizational commitment of medical employees of RSIA Eria Bunda Pekanbaru, organizational culture and work involvement had a significant effect on organizational commitment of medical employees of RSIA Eria Bunda Pekanbaru. Keywords : Organizational Culture, Employee Involvement, Organizational Commitment